Desamarrando o preconceito: um estudo de g??nero, a partir do dispositivo da fotolinguagem - Alencar, V??nia Roseli de (2017)
The asymmetries of gender have been emphasized in public and private camps. This way, some actions researches are necessaries for reducing this situation. The present study looked for analyzing the conception of gender in scholar space, feminine relations, education and technological area from the photolanguage device in the participants??? group of the Fast Girls Project. The objective of this project is to incentive the adolescents of a peripheral region of the Federal District ??? Brazil to ingress in College in the Technological courses. This initiative in question offers a scholarship of one hundred reais (R$100, 00) for each adolescent who integrate the program. This is an incentive of the National Council for Scientific and Technological Development (CNPq) through its Institutional Program for Junior Scientific Initiation Scholarships (PIBIC-JR). The present study looked for analyzing the gender conception in scholar space and the relations among feminine, education and technological area. It was used a photo-language device, which is a mediator object from photos, a reference device to a professional practice and to the research. Another instrument that was used to research was a diary for registers of camp research. The intervention with photo-language was performed with five meetings in the school that were conducted by the educationalist researcher and two Psychology???s students of the Scientific Initiation. In the meetings was discussed the thematic about gender and education ??? to be girl/woman in the scholar camp; the women???s place in education; the impact of the Fast Girls Project; the high school conclusion and the perspectives to the future; women and their insertions in the world of work and in technologic areas. The results revealed that the adolescents wish stopping with the way their mothers and grandmothers have relationship with their companions, with the way they got in the world of work and the fact of not concluding their studies. In the meetings the adolescents had evidenced about the vicissitudes caused by masculine domination that is present still and the women???s burden in relation with their families, increased of the work day hours, like the challenges of the peripheries girls to ingress in the most elevated level of education. The social markers of differences and their visibility emerge, too, like gender questions components. The adolescents have punctuated the relevance of the Fast Girls Project to the group???s participants, besides not all of them feel attraction for courses in Technological areas, they qualified the fact that, by the Project they could to know the university and to have proximity with the women that made their percuss in Engineering. The photo-language device presented like an innovator object to the fomentation of the discussions and the exchanges of the group, made possibly the deconstruction of the feminine idea, education and a work world faced to women. The photo-language like a mediator object promoted a group association chain driven by the photography.